Cultural Pluralism In Indonesia: Continuous Reinventing of Indonesian Islam in Local, National and Global Contexts - Azyumardy Azra (Asia-Pacific Journal on Religion and Society, 2018)
Indonesia is a country consisting of various ethnicities, religions, and races. Multicolored ethnic groups have inhabited for centuries in the country of Indonesia. The interaction between them for decades also gave birth to a pluralist concept, which is a respectful order among them. Pancasila which has become the basis of the Indonesian State proves the existence of cultural diversity as well as the recognition of Indonesian Islam towards the plurality of cultures in Indonesia. Therefore the revitalization of Pancasila with the life and daily reality of Indonesian society is a necessity. In the future, dialogue between cultures and religions that are more concerned with equality is very important.